2014
DOI: 10.1103/physrevd.90.104037
|View full text |Cite
|
Sign up to set email alerts
|

Observables in loop quantum gravity with a cosmological constant

Abstract: An open issue in loop quantum gravity (LQG) is the introduction of a non-vanishing cosmological constant Λ. In 3d, Chern-Simons theory provides some guiding lines: Λ appears in the quantum deformation of the gauge group. The Turaev-Viro model, which is an example of spin foam model is also defined in terms of a quantum group. By extension, it is believed that in 4d, a quantum group structure could encode the presence of Λ = 0. In this article, we introduce by hand the quantum group Uq(su(2)) into the LQG frame… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
92
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(92 citation statements)
references
References 74 publications
0
92
0
Order By: Relevance
“…With a cosmological constant one would, however, expect a vacuum describing a homogeneously curved geometry. There are a number of approaches to incorporate homogeneously curved geometry into the kinematical set-up of (loop) quantum gravity [18][19][20][21]. An important aspect, making such a construction very attractive [22], is that one expects the Hilbert space associated to a fixed triangulation 1 to be finite dimensional.…”
Section: Jhep05(2017)123mentioning
confidence: 99%
See 1 more Smart Citation
“…With a cosmological constant one would, however, expect a vacuum describing a homogeneously curved geometry. There are a number of approaches to incorporate homogeneously curved geometry into the kinematical set-up of (loop) quantum gravity [18][19][20][21]. An important aspect, making such a construction very attractive [22], is that one expects the Hilbert space associated to a fixed triangulation 1 to be finite dimensional.…”
Section: Jhep05(2017)123mentioning
confidence: 99%
“…In addition to Wilson loop operators one can consider grasping operators [18], which usually implement the fluxes, and can be straightforwardly evaluated using (3.3), (3.4). How are these operators geometrically interpreted [21,85]? Do they provide an alternative quantization of (possibly non-exponentiated) flux operators?…”
Section: Jhep05(2017)123mentioning
confidence: 99%
“…In this papier, we provided a first step towards validating the geometrical interpretation of the spin network states of q-deformed loop quantum gravity in 3+1-dimensions [27][28][29][30] as discrete hyperbolic geometry. Indeed we showed that the SB(2, C) Gauss law or closure constraints imposed at the spin network vertices are related to hyperbolic tetrahedra, mimicking the correspondance given by the Minkowski theorem in the flat case between R 3 closure constraints and (convex) polyhedra.…”
Section: Discussionmentioning
confidence: 99%
“…We discuss the splitting of the natural SL(2, C) closure with respect to the Iwasawa decomposition and study the possibility of the reconstruction of the original hyperbolic tetrahedron. Finally, we check that, in the framework of the q-deformed phase for loop quantum gravity [27][28][29], the defined closure relation generates 3d rotations of the normals and of the hyperbolic tetrahedron as expected. …”
mentioning
confidence: 99%
See 1 more Smart Citation